Detection of Aflatoxin M-1 in Human Breast Milk and Raw Cow's Milk in Istanbul, Turkey - (:unkn) unknown (INT ASSOC FOOD PROTECTION, 2009)
This survey was undertaken to determine the extent of aflatoxin M-1 (AFM(1)) contamination in human breast milk and raw cow's milk in Istanbul. Turkey. Samples of human and raw cow's milk were collected randomly and analyzed for AFM(1) using an enzyme-linked immunosorbetn assay and high-performance liquid chromatography with fluorescence detection in which the,samples were cleaned up with immunoaffinity columns. In this study, AFM(1) was detected in 8 (13.1%) of 61 human breast milk samples examined (mean +/- SD level, 5.68 +/- 0.62 ng/liter range, 5.10 to 6.90 ng/liter) and 20 (33.3%) of 60 raw cow's milk samples examined (range, 5.40 to 300.20 ng/liter). Five (8.3%) of the positive raw cow's milk samples had AFM(1) levels (153.52 +/- 100.60 ng/liter; range, 61.20 to 300.20 ng/liter) that were higher than the maximum tolerance limit (0.05 ppb) stipulated by regulations in Turkey and some other countries.
Keywords: OCHRATOXIN-A; EGYPTIAN MOTHERS; CONTAMINATION; IRAN; SAMPLES; CHROMATOGRAPHY; EXPOSURE; PAKISTAN; PROVINCE; CHEESE